The risk of education : discovering our ultimate destiny - Giussani, Luigi (McGill-Queen's University Press, 2019)
"This is an English translation of an Italian work first published in 1995. Based in Milan, Italy, Giussani heads the Communion and Liberation movement and is a council for the Congregation for the Clergy and the Pontifical Council for the Laity. He discusses education in terms of fundamental truths, in particular, the element of faith. It presents the argument that without the fundamental factors of tradition, the young person is merely a fragile leaf separated from its branch."--